A genetic algorithm based approach for economic dispatch in power system / Mohd Rozely Kalil - Kalil, Mohd Rozely (1998)
This project presents a Genetic Algorithm based approach to solve economic dispatch problem in a power system. The Genetic Algorithm developed in the project was tested on two objective functions for optimizing the economic dispatch problem, which are the total generation cost and the incremental cost function. The performances of the two objective functions were compared in term of minimizing the total cost of generation in satisfying the load demand together with the transmission losses.